2019
DOI: 10.14295/oh.v25i2.2011
|View full text |Cite
|
Sign up to set email alerts
|

Pollen viability and stigma receptivity in Swainsona formosa (G.Don) J.Thompson (Fabaceae), an ornamental legume native to Australia

Abstract: Pollen viability and stigma receptivity are prerequisites for successful cross-pollination and seed set in Swainsona formosa. In this study, the pollen viabilities and stigma receptivities was assayed by in vitro pollen germination and simple hand-pollination method on glasshouse-grown plants, respectively. The viability of pollen grains was tested under three different storage conditions: 1) pollen grains were left on the plant in the glasshouse under natural conditions, 2) pollen grains were harvested and ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Cytomixis on meiotic behavior also affects the viability of pollen as observed in wild Himalayan poppy (Meconopsis aculeata Royle) (42). The current study revealed that V. umbellata pollen has a tricolporate pollen -having three distinct pores, which is common to all members of Papilionoideae (43)(44)(45).…”
Section: Pollen Viability Assaysupporting
confidence: 54%
“…Cytomixis on meiotic behavior also affects the viability of pollen as observed in wild Himalayan poppy (Meconopsis aculeata Royle) (42). The current study revealed that V. umbellata pollen has a tricolporate pollen -having three distinct pores, which is common to all members of Papilionoideae (43)(44)(45).…”
Section: Pollen Viability Assaysupporting
confidence: 54%
“…Stigma receptivity plays an important role in successful hybridization. For fertilization to occur, the pollen grains must be in a viable state, and the stigma must be in a receptive condition (Zulkarnain et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Pollen viability and stigma receptivity are two main factors which are crucial in determining the efficiency of reproductive organs to carry out successful pollination which then leads to fertilization and zygote formation (47). The duration and peak period of stigma receptivity as evidenced by peroxidase test, esterase test and in vivo pollen germination is crucial in determining the reproductive success of a plant species (48).…”
Section: Discussionmentioning
confidence: 99%